Oral origin of the placenta microbiome in pregnant women with preeclampsia - Cooper, Shontreal M.; Borgida, Adam; Thacker, Sejal; Hammer, Erica; Hariharan, Amirtha; Kuo, ChiaLing; Blanck, Nyle; Yuan, Hanshu; Panier, Hunter; Lin, Qingqi; Maas, Kendra; Campbell, Winston; et al. (Frontiers in Bacteriology, 2024)
Preeclampsia (PE) is a leading cause of morbidity and mortality in pregnancy with elusive etiology. Patients with PE are thought to be associated with a higher rate of periodontal diseases (PDs) and changes of oral bacteria with targeted PCR techniques. However, few studies have investigated the associations between oral microbiome dysbiosis and secondarily disseminated microbes in the placenta simultaneously in patients with PE. The association between detected microbiome in placenta and systemic inflammation in PE is also unclear. We enrolled 54 pregnant patients with and without PE and PD, and profiled the subgingival and placenta microbiome by the V4 region of 16S rRNA gene sequencing. Systemic inflammatory markers tumor necrosis factor-alpha (TNF-α), C-reactive protein (CRP), lipopolysaccharide binding protein (LBP), and interleukins 6 and 8 (IL-6 and IL-8) in blood were measured by ELISA. We found that PD significantly increased the risk of PE after adjusting for age and smoking status (OR = 2.26, 95% CI = 1.14–4.48, p = 0.024). A combined group of oral-associated bacteria Veillonella, Fusobacterium, Haemophilus, Granulicatella, Streptococcus, Gemella, and Neisseria in placenta had a significantly higher prevalence in women with PE compared to women without PE (53.8% vs. 19.0%, p = 0.018), with the highest prevalence in patients with both PE and PD (58.8%). The relative abundance of Haemophilus, Veillonella, and Fusobacterium in subgingival samples was significantly higher in patients with PE than those without PE. The relative abundance of Haemophilus in subgingival samples was associated with increased risk of PE (OR = 2.11, 95% CI = 1.11–4.52, p = 0.032). Proinflammatory cytokine analysis showed that PE patients with PD had higher blood IL-8 levels than PE patients without PD (p = 0.026). CRP, LBP, and TNF-α showed no statistical difference in patients with and without PE or PD. Blood IL-6 levels were significantly higher in patients with detectable placenta microbiome compared to those without placenta microbiome (p = 0.028). Together, our data suggest a potential oral origin of the placental microbiota present in patients with PE, and the microbiota detected in placenta is associated with increased IL-6 level in the blood.